2015
DOI: 10.1038/bjc.2015.164
|View full text |Cite
|
Sign up to set email alerts
|

Cancer symptom awareness and barriers to symptomatic presentation in England—are we clear on cancer?

Abstract: Background:Low cancer awareness may contribute to delayed diagnosis and poor cancer survival. We aimed to quantify socio-demographic differences in cancer symptom awareness and barriers to symptomatic presentation in the English population.Methods:Using a uniquely large data set (n=49 270), we examined the association of cancer symptom awareness and barriers to presentation with age, gender, marital status and socio-economic position (SEP), using logistic regression models to control for confounders.Results:Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
66
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 39 publications
12
66
3
1
Order By: Relevance
“…This corresponds to the surveys showing that awareness of cancer warning signs is low, especially among young men and lower socio–economic groups [26,27]. In addition, almost a quarter of all cancer patients in England present as emergencies, often with the later stage of cancers and poorer outcomes [28].…”
Section: Discussionsupporting
confidence: 62%
“…This corresponds to the surveys showing that awareness of cancer warning signs is low, especially among young men and lower socio–economic groups [26,27]. In addition, almost a quarter of all cancer patients in England present as emergencies, often with the later stage of cancers and poorer outcomes [28].…”
Section: Discussionsupporting
confidence: 62%
“…This supports the view that British culture's value of stoicism and the “stiff upper lip” is something that women who are more acculturated might adopt. Emotional barriers were consistently more prevalent in all ethnic minority groups compared with White British women, particularly embarrassment, supporting previous research …”
Section: Discussionsupporting
confidence: 83%
“…It was also observed that those who had completed Year 12 education were 5.8 times more likely to report a red patch compared with those with no formal education. A previous study by Niksic et al supported this by showing that participants with no school education were less likely to report the common signs and symptoms of cancer. Park et al found a similar result, with participants with university degrees more likely to identify a correct sign or symptom compared with those with less than Year 10 education.…”
Section: Discussionmentioning
confidence: 80%